I am puzzled by the following example of the application of binomial expansion from Bostock and Chandler's book Pure Mathematics:(adsbygoogle = window.adsbygoogle || []).push({});

If n is a positive integer find the coefficient of x^{r}in the expansion of (1+x)(1-x)^{n}as a series of ascending powers of x.

[itex](1+x)(1-x)^{n} \equiv (1-x)^{n} + x(1-x)^{n} [/itex]

[itex]\equiv\sum^{n}_{r=0} { }^{n}C_{r}(-x)^{r} + x\sum^{n}_{r=0} { }^{n}C_{r}(-x)^{r}[/itex]

[itex]\equiv\sum^{n}_{r=0} { }^{n}C_{r}(-1)^{r} x^{r}+ \sum^{n}_{r=0} { }^{n}C_{r}(-1)^{r}x^{r+1}[/itex]

[itex]\equiv [1-{ }^{n}C_{1}x+{ }^{n}C_{2}x^{2}...+{ }^{n}C_{r-1}(-1)^{r-1} x^{r-1}+{ }^{n}C_{r}(-1)^{r} x^{r}+...+(-1)^{n}x^{n}][/itex]

[itex]+[x-{ }^{n}C_{1}x^{2}+...+{ }^{n}C_{r-1}(-1)^{r-1} x^{r}+{ }^{n}C_{r}(-1)^{r} x^{r+1}+...+(-1)^{n}x^{n+1}][/itex]

[itex]\equiv\sum^{n}_{r=0} [{ }^{n}C_{r}(-1)^{r} + { }^{n}C_{r-1}(-1)^{r-1}]x^{r}[/itex]

The 4th and 5th line seemed a peculiar way of writing it. Were they just trying to demonstrate how the second series is always one power of x ahead?

The last expression seems to require a definition of [itex]{ }^{n}C_{-1}[/itex] which hasn't been defined in the book so I'm guessing I have misunderstood something. Could someone please explain this for me?

Apologies for any typos, I'm using a mobile. Very fiddley.

**Physics Forums - The Fusion of Science and Community**

# Binomial expansion

Have something to add?

- Similar discussions for: Binomial expansion

Loading...

**Physics Forums - The Fusion of Science and Community**